GAMBARAN COOPERATIVE LEARNING TIPE THINK PAIR SHARE UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS - Rukmana, Kholidah Hardiyanti Shinta; Mulyadi, Hari; Utama, Dian Herdiana (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Purpose – This study was conducted to see how application learning model type think pair share to increase critical thinking skillsDesign / methodology / approach – This research used experimental method with quasi experiment, Sample of 70 students of Marketing X class using saturated samples. Collection of data with multiple choice test of critical thinking ability. Data analysis used is frequency distribution.Findings - improving critical thinking skills with the application of cooperative learning type think pair share model Originality - differences were found in research objects and methods, population and sample studies, periods of research, measuring instruments and research results, as well as supporting different theories and references used by previous researchers.repancies found in the object and research methods, population and sample, the study period, measuring tools and research results, as well as the source of theories and foreign journals and books.